Understanding Anxiety in Chronic Kidney Disease: The Role of Haemodialysis Duration and Family Support – A Correlational Study - Aric Vranada; Warsono; Nana Juwita Sari (HealthCare Nursing Journal, 2026)
Chronic kidney disease (CKD) is a progressive and irreversible decline in renal function, often necessitating long-term hemodialysis. Anxiety is a prevalent psychological concern among CKD patients, potentially influenced by treatment duration and the level of family support. This study aimed to examine the correlation between hemodialysis duration, family support, and anxiety levels among patients with CKD at Dr. Kariadi General Hospital, Semarang, Indonesia. A cross-sectional correlational study was conducted involving 89 hemodialysis patients, selected through a non-probability sampling method from total of 165 CKD patients with hemodialysis. Data collection occurred between July 2023 and March 2024, utilizing three instruments: a demographic questionnaire, the Hamilton Rating Scale for Anxiety (HRS-A), and the Family Support Scale (FSS). Data were analyzed using univariate and bivariate approaches, including Spearman’s rank correlation test. A significant negative correlation was found between the duration of hemodialysis and anxiety levels, indicating that patients undergoing hemodialysis for a longer period tended to experience lower anxiety. Similarly, higher levels of family support were significantly associated with lower anxiety scores (p<0.001). Both longer hemodialysis duration and stronger family support are associated with reduced anxiety in CKD patients. Enhancing family involvement and providing consistent education about hemodialysis care may contribute to better psychological well-being in this population.